The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3389/fcell.2015.00053
|View full text |Cite
|
Sign up to set email alerts
|

Developing a functional urinary bladder: a neuronal context

Abstract: The development of organs occurs in parallel with the formation of their nerve supply. The innervation of pelvic organs (lower urinary tract, hindgut, and sexual organs) is complex and we know remarkably little about the mechanisms that form these neural pathways. The goal of this short review is to use the urinary bladder as an example to stimulate interest in this question. The bladder requires a healthy mature nervous system to store urine and release it at behaviorally appropriate times. Understanding the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 77 publications
2
41
0
Order By: Relevance
“…The current results correspond with observations concerning the development of the innervation of the urinary bladder in human foetuses (Keast et al. ), which revealed that DβH‐ or VAChT‐positive nerve structures appear much earlier than those expressing CGRP and/or SP (Keast et al. ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The current results correspond with observations concerning the development of the innervation of the urinary bladder in human foetuses (Keast et al. ), which revealed that DβH‐ or VAChT‐positive nerve structures appear much earlier than those expressing CGRP and/or SP (Keast et al. ).…”
Section: Discussionsupporting
confidence: 92%
“…), urinary bladder (Keast et al. ) and gut in human (Faussone‐Pellegrini et al. ) and urinary tract in the dog foetuses (Arrighi et al.…”
Section: Introductionmentioning
confidence: 99%
“…Bladder afferents contain a variety of neuropeptides, including: CGRP, Sub P, vasoactive intestinal polypeptide, pituitary adenylate cyclase-activating polypeptide, cholecystokinin and enkephalins (Arms and Vizzard, 2011; de Groat et al, 1983; Keast and De Groat, 1992; Vizzard, 2000d, 2001). The innervation of the urinary bladder arises primarily from neuronal cell bodies located at a distance from the urinary bladder; however, some neuronal cell bodies appear transiently in the bladder wall during development and early postnatal life, with few remaining by adulthood (Keast et al, 2015; Zvarova and Vizzard, 2005). The functions of these intramural ganglion neurons are not known but their chemical phenotype more closely resembles autonomic rather than sensory neurons (Forrest et al, 2014; Keast et al, 2015; Zvarova and Vizzard, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The innervation of the urinary bladder arises primarily from neuronal cell bodies located at a distance from the urinary bladder; however, some neuronal cell bodies appear transiently in the bladder wall during development and early postnatal life, with few remaining by adulthood (Keast et al, 2015; Zvarova and Vizzard, 2005). The functions of these intramural ganglion neurons are not known but their chemical phenotype more closely resembles autonomic rather than sensory neurons (Forrest et al, 2014; Keast et al, 2015; Zvarova and Vizzard, 2005). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation